2016
DOI: 10.1186/s12974-016-0771-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-15a/16 reduces retinal leukostasis through decreased pro-inflammatory signaling

Abstract: BackgroundHyperglycemia is a significant risk factor for diabetic retinopathy and induces increased inflammatory responses and retinal leukostasis, as well as vascular damage. Although there is an increasing amount of evidence that miRNA may be involved in the regulation in the pathology of diabetic retinopathy, the mechanisms by which miRNA mediate cellular responses to control onset and progression of diabetic retinopathy are still unclear. The purpose of our study was to investigate the hypothesis that miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 34 publications
2
55
0
1
Order By: Relevance
“…6). These findings are in agreement with prior reports [27,32]. Moreover, knockdown of A2aAR by transfection with miR-15 and A2aAR-siRNA induced the nuclear translocation of NF-κB p65, resulting in upregulation of IL-8 and IFN-γ expression.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…6). These findings are in agreement with prior reports [27,32]. Moreover, knockdown of A2aAR by transfection with miR-15 and A2aAR-siRNA induced the nuclear translocation of NF-κB p65, resulting in upregulation of IL-8 and IFN-γ expression.…”
Section: Discussionsupporting
confidence: 83%
“…MiR-15 regulates TNF-α-mediated apoptosis in patients with liver failure [26]. Ye et al [27] suggested that miR-15a inhibits NF-κB, IL-1β, and TNFα signalling in retinal endothelial cells. A recent report suggested that the 3′-UTR of A2aAR harbours binding sites for miR-15 and miR-16 [21].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were done using miR15a endothelial cell specific knockout mice (Ye et al, 2016) and overexpressing mice (Ye et al, 2017). Mice of both sexes at 3 months of age were used.…”
Section: Methodsmentioning
confidence: 99%
“…REC grown in high glucose were transfected with miR15a mimic (hsa-miR15a-5p) and a negative control (Ye et al, 2016). In addition, some normal glucose and high glucose control cell groups were treated with oligofectamine only.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation